Aproximación a los documentos fiscales de la Cámara Pontificia. Dos litterae conservadas en el archivo de la Catedral de León - Domínguez Sánchez, Santiago (Estudios humanísticos. Geografía, historia y arte, 1997)
In this paper two document on papal Chamber are analyzed, using the traditional method of the diplomatic science. Our analysis is similar to the typical studies on the papal Chancery documents. The refered documents about pontifical Chamber are deposited in León cathedral’s archive